Transcranial stimulation over right inferior frontal gyrus increases the weight given to private information during sequential decision-making. Issue 1 (27th November 2018) - Niu, Xiaofei; Li, Jianbiao; Browne, Glenn J; Li, Dahui; Cao, Qian; Liu, Xiaoli; Wang, Guangrong; Wang, Pengcheng
Abstract: Decision makers often follow other similarly situated people in making decisions, creating a sequential decision-making context. Although rational behavior is often to make the same choice as previous decision makers, which can result in an information cascade, people may assign inappropriately higher weight to their own private information and discount public information about predecessors' choices. Recent findings suggest that overweighting private information may be associated with increased activities in the inferior frontal gyrus (IFG). In the present study, we employed transcranial direct current stimulation (tDCS) and developed a computational model to examine the causal relationship between right IFG (rIFG) and overweighting private information. Specifically, we applied three types of tDCS over rIFG while participants were completing a sequential decision-making task. Our results showed that anodal stimulation significantly increased the weight given to private information and decreased the response time in making a decision when private information conflicted with public information, but cathodal stimulation did not have such impacts. Importantly, the effect of anodal stimulation was significant in some conditions when information conflict or task difficulty reached a threshold that might trigger cognitive control-related processes. Our findings revealed the important role of rIFG in trade-off between considering private and public information during sequential decision-making.